Depuration of Heavy Metals with Nanoparticle-Sized Active Charcoal from Coconut Shell (Cocos nucifera) in Blood Cockles (Anadara granosa) - Putri Alia Paramitha; Yusuf Taufik Hidayat; Kamiliya Zahrah Taher; Intan Cahyarini; Boedi Setya Rahardja; A Shofy Mubarak; Kustiawan Tri Pursetyo (Universitas Airlangga, 2022)
Anadara granosa are one of the benthic organisms that are frequently reported because contained heavy metals because of water pollution. This is because A. granosa is a feeder filter so that accumulates heavy metals in its body. Reduce the levels of heavy metals with activated charcoal from coconut shells in the absorbance process using the depuration method. It is re-optimized with the use of nano-active charcoal. The goal was to determine the effect of concentrations of nano-active charcoal from coconut shells on the heavy metal content of A. granosa. Stages of this reserch, namely charcoal activation, ultrasonication, SEM testing, blood shell depuration, and heavy metal testing. Based on the results of the Scanning Electron Microscope (SEM) Test it is known that the charcoal particles are sized 10-9 nm. The types of heavy metals found included hydrargyrum (Hg) 0.0009 mg/kg, cadmium (Cd) 0.62 mg/kg, and plumbum (Pb) 1.82 mg/kg. Heavy metals with lowest content is found in P5 (active charcoal concentration of 15% of the sample weight) of mercury (Hg) 0.0002 mg/kg; cadmium (Cd) 0.1 mg/kg; and lead (Pb) 0.373 mg/kg. This shows that the higher concentraion of activated charcoal given, the lower heavy metal content.